Acquired Factor X Deficiency in a Patient with Amyloidosis - Korsan-Bengtsen, Kristoffer; Hjort, Peter F; Ygge, Johan (Thrombosis and Haemostasis, 1962)
A patient with extensive amyloidosis and a selective factor X deficiency is described. The following observations indicate that the factor X deficiency in this case is not inherited.1. The first symptoms of a bleeding tendency appeared at an age of 50 years.2. The patient’s four children had no clotting defect.3. After infusion of 1 liter of fresh plasma no increased factor X activity was observed. No anticoagulants could be demonstrated in vitro.